Inside the Fictional Mind: A Cognitive Stylistic Analysis of Arya Stark’s Mental Models in the Series of “A Song of Ice and Fire” - Al-Musawi, Inaam Abdul-Jabbar Abdul-Kadhim; Ijam, Dunya Muhammed Miqdad (Journal of Cultural Analysis and Social Change, 2026)
This paper examines the cognitive stylistic perspectives of Arya Stark’s mental models construction in the series of A Song of Ice and Fire (ASOIAF). It investigates how the linguistic and stylistic cues externalize Arya’s evolving awareness, identity, and morality. Drawing on frameworks from cognitive stylistics, particularly Stockwell’s (2020) model of mind-modelling and Johnson-Laird’s (1980) theory of mental models, the analysis investigates Arya’s chapters across five novels of the series. The paper identifies how the cognitive representations of selfhood are constructed, revised, updated, and disrupted through language, narrative perspectives, and embodied metaphors. This is accomplished through attentive reading and cognitive stylistic analysis. The results demonstrate that Arya’s cognitive trajectory progresses from a conflict schema of gender and identity to adaptive survival cognition and moral reconstruction. Each stage of her cognitive development is marked by a particular mental model, such as the mental model of “sword identity, wolf assassin, and no one” identities. The constructed mental models reveal a deep cognitive interplay among past trauma, disguise, and self-awareness. The analysis shows that Martin’s linguistic style and narrative framing guide readers to engage in complex mind-reading processes that mirror Arya’s internal shift in self-perception. The constructed mental models demonstrate that Arya’s cognitive evolution reflects the integration of identity, morality, and survival in narrative cognition, underscoring the role of fiction as a simulation of human mental life. The findings contribute to cognitive stylistic scholarship by demonstrating how readers’ construction of mental models parallels a character's evolving consciousness, offering insight into the cognitive realism and emotional depths of Martin’s narrative craft.